Dismantling Culture and System of Settings: A Critical Conceptual Framework for Reading the Built Environment - Susilo Kusdiwanggo (Jurnal Lingkungan Binaan Indonesia, 2026)
Although culture is widely recognized as shaping the built environment, scholarship often remains descriptive and methodologically unclear about how cultural determinants become spatially manifest and ideologically consequential. Addressing this gap, especially with respect to vernacular settings, this study proposes an integrated framework that couples dismantling culture with the system of settings construct to operationalize culture for spatial reading. Using a conceptual-analytic method (critical literature reading and theoretical synthesis), culture is decomposed into values, norms, lifestyles, and activity systems and aligned with system of settings analysis, which treats environments as ordered relations among space, time, activity, and communication. The framework shows that (1) culture becomes spatially legible through staged translation via activity systems; (2) the system of settings mediates cultural registration across fixed, semi-fixed, and non-fixed features; (3) typologies (vernacular, spontaneous, traditional, modern-formal) differ by cultural embeddedness; and (4) translation is hermeneutic, delimiting possibilities rather than prescribing form. These results provide an interpretive grammar for culturally responsive design and post-occupancy evaluation and motivate subsequent empirical testing through comparative field studies.